Genitourinary tuberculosis in the structure of autopsy morphological findings in deceased patients at the late stages of HIV infection - L. V. Puzyreva; A. V. Mordyk; S. A. Rudenko (Вестник урологии)
Introduction. The problem of tuberculosis (TB) has not lost its significance due to the overlapping epidemic of HIV infection and the addition of specific lesions at its late stages. It is due to the lack of adherence to antiretroviral therapy in a large number of patients. The high mortality rate in HIV-associated TB requires an increase in the interest of all doctors for the early detection of various TB localizations against the background of HIV, allowing the patient to be cured. For urologists, information on the frequency of genitourinary TB in HIV patients is of interest to improve its diagnosis.Purpose of the study. To identify the proportion of genitourinary TB in the structure of the specific lesions in patients with HIV-associated TB.Materials and methods. The case-records of 115 deceased patients with a combination of HIV infection and TB were retrospectively analyzed using a continuous method. The number of men among them was 81.7 ± 3.6% (94). The average age of men was 37.1 ± 27.2 years, women — 31.9 ± 6.3 years. The research results were processed statistically.Results. The average period from the moment of HIV infection detection to the registration of a lethal outcome was 2.8 ± 1.3 years, from the moment of TB diagnosis — 6.96 ± 7.3 years. The majority of patients with HIV infection had a stage of secondary diseases (93.1 ± 2.4%). At the time of admission to the TB dispensary, the average CD4 + lymphocyte level was 131.06 ± 75.8 cells/pL, 10.03 ± 2.5%. Anti-retroviral therapy was observed only in 19 (16.5 ± 3.5%) patients. In deceased patients disseminated pulmonary TB was more often verified at autopsy — 52.2 ± 4.7%, miliary — 7.8 ± 2.5%, infiltrative — 11.3 ± 3.0%. In patients with disseminated and miliary pulmonary TB, foci of dropout were often observed in the spleen (71.7 ± 5.8% and 55.6 ± 16.6%) and liver (46.7 ± 6.4% and 33.3 ± 15,7%). The kidney damage occurred in 60.0 ± 6.3% of patients with disseminated and 44.4 ± 16.6% miliary pulmonary TB. Kidneys TB was confirmed by bacterioscopic urine examination in three cases only (2.6 ± 1.5%) during life. Prostate TB was confirmed by analysis of expressed prostatic secretion on Mycobacterium tuberculosis (2.6 ± 1.5%) and was combined with kidney TB. The lesions of the lymphatic system during life were exposed in 17.4 ± 3.5% of patients. A pathomorphological examination revealed TB of intrathoracic lymph nodes in 37.4 ± 4.5%, intra-abdominal lymph nodes — in 22.6 ± 3.9%, peripheral — 6.1 ± 2.2%, more often in miliary and disseminated pulmonary TB. TB meningitis was registered in 31 cases as well as meningoencephalitis in 32 patients during life and at autopsy, respectively. Intestinal TB was confirmed by autopsy in 9.6 ± 2.7% of patients; during life, it was accompanied by the detection of the pathogen in the feces. The pancreatic TB was detected in 2.6 ± 1.5%, TB spondylodiscitis in 1.7 ± 1.2%, myocardial TB in 0.9 ± 0.9% and pericardium TB in 0.9 ± 0.9% cases.Conclusion. Thus, generalized TB is diagnosed in patients in the late stages of HIV infection, in the structure of which kidney damage is in second place, yielded only to spleen damage. Obtaining this information should form the alertness of urologists in terms of detecting and diagnosing genitourinary TB in patients with HIV infection.